Synthesis, Spectroscopic, and Biological Studies on New Zirconium(IV) Porphyrins with Axial Ligand - Gauri D. Bajju; Gita Devi; Sapna Katoch; Madhulika Bhagat; Deepmala; Ashu; Sujata Kundan; Sunil Kumar Anand (Bioinorganic Chemistry and Applications)
A series of parasubstituted tetraphenylporphyrin zirconium(IV) salicylate complexes (SA/5-SSAZr(IV)RTPP, R = p-H, p-CH3, p-NO2, p-Cl, SA = salicylate, and 5-SSA = 5-sulfosalicylate) have been synthesized, and the spectral properties of free base porphyrins, their corresponding metallated, and axially ligated zirconium(IV) porphyrin compounds were compared with each other. A detailed analysis of ultraviolet-visible (UV-vis), proton nulcear magnetic resonance (1H NMR) spectroscopy, infrared (IR) spectroscopy, and elemental analysis suggested the transformation from free base porphyrins to zirconium(IV) porphyrins. The ability of the metal in this complex for extra coordination of solvent molecules was confirmed by ESI-MS spectra. Besides the fluorescence, cyclic voltammetry, and thermogravimetric studies, the complexes were also screened for antimicrobial and anticancer activities. Among all the complexes, 5-SSAZr(p-NO2TPP) shows high antibacterial activity.